Protection during production: Problems due to prevention? Nail and skin condition after prolonged wearing of occlusive gloves. Issue 7 (18th April 2017) - Weistenhöfer, Wobbeke; Uter, Wolfgang; Drexler, Hans
ABSTRACT: Wearing of occlusive gloves during the whole working shift is considered a risk factor for developing hand eczema, similar to wet work. Moreover, the increased hydration due to glove occlusion may lead to brittle nails. Two hundred and seventy clean room workers, wearing occlusive gloves for prolonged periods, and 135 administrative employees not using gloves were investigated. This included a dermatological examination of the nails and the hands, using the Hand Eczema ScoRe for Occupational Screening (HEROS), measurement of transepidermal water loss (TEWL), and a standardized interview. Of the clean room workers, 39%, mainly women, reported nail problems, mostly brittle nails with onychoschisis. Skin score values showed no significant differences between HEROS values of both groups. TEWL values of exposed subjects were similar to TEWL values of controls 40 min after taking off the occlusive gloves. In a multiple linear regression analysis, male gender and duration of employment in the clean room were associated with a significant increase in TEWL values. The effect of occlusion on TEWL seems to be predominantly transient and not be indicative of a damaged skin barrier. This study confirmed the results of a previous investigation showing no serious adverse effect of wearing of occlusive gloves on skin condition without exposure to additional hazardous substances. However, occlusion leads to softened nails prone to mechanical injury. Therefore, specific prevention instructions are required to pay attention to this side effect of occlusion.